Effect of expiratory positive airway pressure on tidal volume during non-invasive ventilation. (May 2017) - Kinnear, W; Watson, L; Smith, P; Johnson, L; Burrows, S; Colt, J; Sovani, M; Khanna, A
During non-invasive ventilation (NIV), tidal volume ( V t ) will depend upon the difference between inspiratory and expiratory positive airway pressure (IPAP and EPAP, respectively), provided the respiratory muscles are relaxed and the lungs and chest wall therefore move along their passive pressure–volume curves. To test this hypothesis, we studied the effect of increasing EPAP during pressure-controlled modes of NIV in 30 long-term ventilator users (10 each with scoliosis, obesity hypoventilation or neuromuscular disorders). While maintaining the same IPAP, addition of 5 cmH2 O of EPAP reduced mean V t by 167 ml; 10 cmH2 O reduced V t by 367 ml. This pattern was seen in all three patient groups. EPAP has several potential advantages, for example maintaining upper airway patency, preventing basal atelectasis and facilitating triggering. EPAP does, however, appear to reduce V t . Decreasing EPAP is an alternative to increasing IPAP if measurements of gas exchange during NIV indicate that ventilation is inadequate.